Identifying clinical features of fluid status among children with suspect dengue in Indonesia - Agni Laili Perdani; Agus Hendra; Astri Mutiar; Winda Heriani (Malahayati International Journal of Nursing and Health Science, 2021)
Background: The incidence of dengue had significantly increasing every years in Indonesia. Children is vulnerable population and have higher risk develop to shock complication from dengue. This infectious disease can cause several symptoms such as nausea or vomiting, no appetite, leakage of blood plasma and the patient may experience hypovolemic shock. One of the factors that can affect dengue virus infection is nutritional and fluid status.Purpose: To identifying clinical features of fluid status among children with suspect dengue in IndonesiaMethod: A descriptive quantitative method and conducted at the public health center in West Java Indonesia. The sample taken by a convenience sampling method. Inclusion criteria were children aged 1-14 years old diagnosed with dengue infection and hospitalized in Pediatric Ward.Results: Finding that the respondents diagnosed with dengue fever (DF) had experienced dehydration of 86.8%. and diagnosed with dengue hemorrhagic fever (DHF) had experienced dehydration of 83.3%Conclusion: Most children with dengue infections have dehydrated. This condition is because of symptoms such as nausea, vomiting, lack of appetite, abdominal pain, and then following by difficulty taking oral fluid.